Investigation of the Effect of Dilation Angle of Soil on the Performance of Grouted Tieback Under Axial Static Load by Analytical Approach - Mekki Feriel (Selected Scientific Papers: Journal of Civil Engineering)
Studies on how non-associated flow rules affect the performance of grouted tieback using the upper bound of limit analysis theory are relatively rare. In this paper, the expression of the collapse load of a single, inclined, rough grouted tieback subjected to axial static load placed in a frictional soil was determined by constructing a failure mechanism by combining a non-associated flow rule in the upper bound limit analysis technique and the linear Mohr-Coulomb yield criterion. The effects of variation of dilation angle, the soil friction angle, the grouted tieback’s angle of inclination, the bonded length, and the diameter of bonded length on the ultimate load were investigated. The results obtained from the present study clearly indicated that the dilation angle, the soil friction angle, the grouted tieback’s angle of inclination, and the bonded length all significantly affect the collapse load but the bonded length’s diameter has no effect on the critical load.